Teammate Social Support as a Predictor of Fear of Returning to Play in Collegiate Athletes - Ranielle Lingan; Marvin Luis C. Sabado (CV. AULIANTECH, 2026)
This study examined whether social support from teammates predicts the fear of returning to play (FRTP) among collegiate athlete post-rehabilitation. Using a quantitative approach, data were collected from 86 collegiate athletes through the Social Support Questionnaire (SSQ) and the Fear to Return Sport Scale (FRESS). Linear regression analysis revealed that the model accounted for 28% of the variance in fear levels (R2 = .28, p < .001). Crucially, results indicated that satisfaction with support was a significant negative predictor of fear (β = -.48, p < .01), whereas the number of supportive teammates was not a significant predictor (p = .24). These findings suggest that the quality of peer interactions is more influential than the quantity of supporters in mitigating psychological barriers. The results inform the implementation of team-based communication workshops and peer-support training to optimize psychological recovery. Future research should consider variables outside this scope, such as the timing and type of support provided alongside injury severity. By prioritizing high-quality functional support, athletic programs can better facilitate a resilient transition back to competition.